Design of interactive learning courseware for sorting algorithms - Gurwinder Singh (2018)
E-learning is increasingly getting popular nowadays due to many reason. One of the reasons being convivence. Sorting algorithm is a topic taught in EE2008. Many NTU modules are switching over to online platform instead of face-to-face lectures. This project will implement E-learning system Learning Management System Moodle. The project will adopt both synchronous and asynchronous teaching features. In addition to that this project will include quizzes with automated marking and achieve student participation through forum discussion or even lecture recording. Interactive lecture recording will be implemented, live lecture and tutorial will also be included.